PELAKSANAAN GERAKAN LITERASI SEKOLAH BERBASIS KEARIFAN LOKAL UNTUK MENGEMBANGKAN KARAKTER PESERTA DIDIK - Novi Resti Hemayati; Susilawati Susilawati (Jurnal PGSD, 2020)
The School Literacy Movement (GLS) is an overall effort to make schools as a learning organization whose make all residents at school are literate throughout their lives through public involvement. Various parties who can drive this activity include school residents, stakeholders and the community. It aims to jointly own, carry out, and make this movement an important part of life. The aims of this research are to determine whether the existence of school literacy movement based on local wisdom can develop the character of students, how to link the school literacy movement based on local wisdom in order to develop the character of students in and how teachers’ perceptions of and other stakeholders regarding the school literacy movement. This research is using qualitative research. The subjects in this research are the students of SDN 2 Tuk and several other informant. The research subjects taking by using purposive sampling technique. This literacy activities based on local can develop the character of students. In this activity, researcher and teachers class have provided literacy-based learning by giving assignments that related to the value of local wisdom, as writing how to make emping and writing the history of the village of Tuk. Keywords: School-Literacy-Movement (GLS), local-wisdom, character.